2014
DOI: 10.1002/btpr.1980
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing binding capacity for protein A chromatography

Abstract: Advances in cell culture expression levels in the last two decades have resulted in monoclonal antibody titers of ≥10 g/L to be purified downstream. A high capacity capture step is crucial to prevent purification from being the bottleneck in the manufacturing process. Despite its high cost and other disadvantages, Protein A chromatography still remains the optimal choice for antibody capture due to the excellent selectivity provided by this step. A dual flow loading strategy was used in conjunction with a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Unlike its predecessors in the Protein A resin family, the new Protein A ligand on MabSelect SuRe was designed to tolerate alkali solutions by substituting the alkali sensitive amino acid regions with more stable ones . MabSelect SuRe LX has the same functional alkali stable ligand but at much higher density on the bead matrix allowing for higher binding capacities . This permits for the use of more stringent cleaning agents, such as sodium hydroxide, which were once off limits to the Protein A step .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike its predecessors in the Protein A resin family, the new Protein A ligand on MabSelect SuRe was designed to tolerate alkali solutions by substituting the alkali sensitive amino acid regions with more stable ones . MabSelect SuRe LX has the same functional alkali stable ligand but at much higher density on the bead matrix allowing for higher binding capacities . This permits for the use of more stringent cleaning agents, such as sodium hydroxide, which were once off limits to the Protein A step .…”
Section: Introductionmentioning
confidence: 99%
“…Recent analysis with a 5 g/L bioreactor titer indicated that buffer/product tank volumes would be the primary bottlenecks in the downstream process . A variety of solutions have been evaluated to address these bottlenecks: inline buffer dilution, in‐line product concentration, high‐capacity Protein A, and no‐salt hydrophobic interaction chromatography . These allow for incremental increases in the capacity of the existing purification trains; however, recent improvements in cell culture processes have allowed companies to achieve these higher titers with a shorter duration in the production bioreactor, forcing downstream development groups to explore ways to purify the product even more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Also other methods used for the structural determination of protein‐surface interactions require a sample pretreatment resulting in non‐native process conditions as described in the review by Rabe et al. .…”
Section: Introductionmentioning
confidence: 99%
“…We used MabSelect SuRe (GE Healthcare), a popular protein‐A chromatography resin, as the model system and small angle X‐ray scattering (SAXS) as the probing method. Cross‐linked, porous agarose beads 85 μm in diameter are characterized by a rigid, high‐flow backbone matrix and a tetrameric ligand of synthetically engineered B‐domains, called Z‐domain, immobilized via short linkers . From equilibrium binding capacity and ligand density it was derived that on average 3.3 antibody molecules are bound to one MabSelect SuRe protein‐A ligand .…”
Section: Introductionmentioning
confidence: 99%